Hubungan antara Upah Karyawan dengan Produktivitas kerja Karyawan Pada PT. Polymatech Indonesia - pradha prahesty (POLITEKNIK PIKSI GANESHA, 2020)
This study aims to analyze and reveal the relationship between wages and employee productivity at PT. Polymatech Indonesia. This study uses a survey method with a correlational approach and uses secondary data (independent variables) and secondary data (dependent variables). The use of this method is intended to measure the degree of closeness between wages and employee productivity. Correlation approach is used to see the relationship between two variables, namely the independent variable (wages), amounting to 51 people and processed by the path analysis method and using the SPSS 16 Program. The results obtained that there is a positive influence between the variable wages either partially or jointly on employee productivity in PT. Polymatech Indonesia. Keywords: Wages, Work Productivity, employees.